Fiber Reinforced Composites and their Application in the Contemporary Dentistry - M. Oudová; J. Krňoulová (Czech Dental Chamber, 2013)
Objectives: The synthetic fiber content significantly improves some physical properties of composite materials, such as tension and flexural resistence. These materials are known as the fiber reinforced composites. They have a wide spectrum of applications in many fields, including medicine, thanks to their low weight and a plethera of other advantageous mechanical properties. They are used in dentistry to provide greater range of favourable alternatives to many standard treatment methods. The basic components of fiber reinforced composites are resin matrix and fibers (nonimpregnated or preimpregnated) and silans, that work as bonding agents between matrix and fibers. The spatial distribution of fibers is also important for the quality of the material; the internal architecture of the fiber beams can be either unidirectional, braided or woven. The glass and polyethylene fibers are usually used as the reinforcement of material. The shapes of the materials for use in dentistry are commonly either posts or ribbons. The design of the products reflects their specific applications. The fiber reinforced composites are most frequently used in prosthetic dentistry for the post and core fabrication as well as for fabrication of temporary and permanent dentures. In periodontology and dentoalveolar surgery they are used for fabrication of stabilization splints with short-term or long-term usage, and in orthodontics as retainers after completion of the active treatment period. Contraindications of their include poorly cooperating patient, wet operating field and some parafunctions, such as bruxism. The favourable mechanical as well as aesthetic properties are the main advantages of the fiber reinforced composites. Other advantages include relatively low costs, the possibility of direct fabrication without any laboratory phase during prosthetic treatments and the long-term durability of material. Practical working procedures have previously been discussed in literature that reiterate the fact that a complete knowledge of the material's properties and their indications is essential for their clinical use.